Infographics for the Elephant Education Centre, Way Kambas National Park - Februandari, Asmarani; Nawing, Aditya Yuwana (Jurnal Abdimas Pariwisata, 2025)
The creation of infographics for the Elephant Education Information Center in Way Kambas National Park (WKNP) is part of a community service program that aims to support the revitalization of the information center and introduce new conservation-based tourism concepts. This activity aims to increase visitor awareness of conservation, animal welfare, and the role of buffer village communities in ecotourism management. The methods used include data collection through interviews, focus group discussions (FGDs) and field observations to develop effective and educational infographic concepts and designs. The result of this activity is the development of 12 infographic panels that display information related to the biodiversity of WKNP, the transformation of tourism in PLG, and the contribution of village communities in ecotourism. The resulting infographics are expected to be a visual communication medium that will improve tourists' understanding of conservation, as well as strengthen WKNP's image as a sustainable tourism destination focused on environmental and community well-being.